2016
DOI: 10.1021/acsmacrolett.6b00491
|View full text |Cite
|
Sign up to set email alerts
|

Highly Emissive Excimers by 2D Compression of Conjugated Polymers

Abstract: Interactions between π-conjugated polymers are known to create ground-state aggregates, excimers, and exciplexes. With few exceptions, these species exhibit decreased fluorescence quantum yields relative to the isolated polymers in liquid or solid solutions. Herein, we report a method to assemble emissive conjugated polymer excimers and demonstrate their applicability in the detection of selected solvent vapors. Specifically, poly­(phenylene ethynylene)­s (PPEs) with amphiphilic side chains are organized in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…30 The change of stacking direction and distance often brings different emission efficiency. 31 Therefore, tunable conformation and controlled crystal growth are crucial for understanding the phosphorescence emission efficiency of organic species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 The change of stacking direction and distance often brings different emission efficiency. 31 Therefore, tunable conformation and controlled crystal growth are crucial for understanding the phosphorescence emission efficiency of organic species.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al reported that coassembled crystals could show higher emission efficiency than the single molecular crystals . The change of the stacking direction and distance often leads to different emission efficiencies . Therefore, tunable conformation and controlled crystal growth are crucial for understanding the phosphorescence emission efficiency of organic species.…”
Section: Introductionmentioning
confidence: 99%
“…[15,16] The other type of sidechain is a branched triethylene glycol monomethyl ether and octyl group ("B" in Figure 1b), which was chosen from the previous report. [17] Based on the combination of two types of sidechains, we synthesized three PPEs: P1 with alternate A-B, P2 with A-A, and P3 with B-B as shown in Figure 1. The number ratio of triethylene glycol to octyl per repeat unit is 6:2 (P1), 8:0 (P2), and 4:4 (P3).…”
Section: Introductionmentioning
confidence: 99%
“…The choice of the amphiphilic PPE is critical to promote the proper organizations. Although energy transfer is efficient in the solid state, aggregation-induced quenching of singlet excitons is notoriously common and can lower the exciton diffusion lengths, giving diminished fluorescence quantum yields. , We previously showed that PPEs having amphiphilic side chains displayed novel behavior wherein the compressed monolayers at the air–water interface formed highly emissive excimers with the increase in relative quantum yields compared to noncompressed states . Therefore, we have targeted this system for further applications by functionalization with low-energy emissive perylene dye end groups (Figure ).…”
mentioning
confidence: 99%